Characteristics and microscopic mechanisms of smoke emissions of OMMT/SBS-modified asphalt - Wanhong Yang; Zhenghao Zhang; Xiaolong Yang; Xiaofan Jia; Yixin Jiang (Environment International)
Nanomaterials are increasingly being used in road engineering with the development of road construction technology. The smoke suppression performance of asphalt can be substantially improved using organic nano-montmorillonite (OMMT)/styrene–butadiene–styrene (SBS) block modifiers. Pyrolysis gas chromatography–mass spectrometry (PY-GC–MS), fluorescence microscopy (FM), thermogravimetric analysis (TG), and gel permeation chromatography (GPC) were used to explore the characteristics and microscopic mechanisms of flue gas emissions. The addition of OMMT effectively reduced the emissions of carbon dioxide and Volatile Organic Compounds (VOCs) in asphalt flue gas, as well as increased the SBS swelling degree in the asphalt matrix and the compatibility between the SBS and asphalt matrix. The stable interlayer structure formed via OMMT/SBS co-modification effectively inhibited the release of VOCs during the thermal decomposition of asphalt, being more environmentally friendly because of the reduction in emissions compared with traditional asphalt. The SBS, OMMT, and asphalt matrix is a physically modified mixture. The incorporation of OMMT increases the macromolecule content in the modified asphalt, showing that OMMT inhibited the decomposition of asphalt macromolecules into smaller molecules, thus reducing the release of VOCs. Including the appropriate macro and small molecules helps strengthen the ability of asphalt to resist permanent deformation at high temperatures, maintain its flexibility, and effectively prevent cracking at low temperatures.